Analisis Faktor-Faktor yang Mempengaruhi Safety Climate pada Facility Management Services Area Sumbagsel - Nugraha Juliyanda; Novrikasari Novrikasari; Hamzah Hasyim; Yuanita Windusari; Elvi Sunarsih; Iche Andriyani Liberty (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the factors that affect the safety climate in the work environment of the Facility Management Services Area of South Sumatra. The safety climate is a shared perception of employees about the importance of occupational safety that reflects management's commitment and individual behavior to the application of safety principles. The research method used is a quantitative approach with a survey design using questionnaires distributed to employees in various operational divisions. The variables analyzed included safety leadership, safety communication, safety training, employee engagement, and organizational policies on safety. The data was analyzed using multiple linear regression to see the influence of each variable on the safety climate. The results showed that safety leadership and safety communication have a significant influence on the formation of a positive safety climate, while safety training and organizational policies provide an indirect influence through increased employee participation. In addition, this study also revealed that the relationship factor between workers also strengthens the overall perception of safety. These findings underscore the importance of the role of management and effective communication in building a sustainable safety culture in the facility management sector.